2021
DOI: 10.1097/ccm.0000000000004821
|View full text |Cite
|
Sign up to set email alerts
|

Derivation and Validation of an Ensemble Model for the Prediction of Agitation in Mechanically Ventilated Patients Maintained Under Light Sedation

Abstract: OBJECTIVES: Light sedation is recommended over deep sedation for invasive mechanical ventilation to improve clinical outcome but may increase the risk of agitation. This study aimed to develop and prospectively validate an ensemble machine learning model for the prediction of agitation on a daily basis. DESIGN: Variables collected in the early morning were used to develop an ensemble model by aggregating four machine learning algorithms including suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…Early assessment of the prognosis of patients with AFLP may play an important role in improving maternal and fetal survival ( 4 ), and predictive analytics for risk stratification can help to improve patients management in critical care setting and add some reference for this statement ( 5 7 ). Previous clinical studies on AFLP, largely based on a small number of patients owing to its low prevalence, have found significant differences in its epidemiology ( 1 , 8 ), symptoms ( 9 ), complications ( 9 ), and outcomes ( 1 , 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Early assessment of the prognosis of patients with AFLP may play an important role in improving maternal and fetal survival ( 4 ), and predictive analytics for risk stratification can help to improve patients management in critical care setting and add some reference for this statement ( 5 7 ). Previous clinical studies on AFLP, largely based on a small number of patients owing to its low prevalence, have found significant differences in its epidemiology ( 1 , 8 ), symptoms ( 9 ), complications ( 9 ), and outcomes ( 1 , 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…David et al used machine learning algorithms to improve the cardiovascular risk prediction of patients with end-stage renal disease on hemodialysis ( de Gonzalo-Calvo et al, 2020 ). Michalis et al also found that, based on machine learning algorithms, using volatile organic compounds in exhaled gas as predictors distinguishes lung cancer from other lung diseases or healthy individuals well ( Zhang Z. et al, 2021 ). We used the four machine learning algorithms to develop the EAS predictive model.…”
Section: Discussionmentioning
confidence: 99%
“…However, the LG-based approach fails to consider the complex non-linear interactions between variables, which can be captured by more sophisticated model algorithms, thus improving the accuracy of risk prediction. Recently, machine learning has been widely applied to the development of clinical tools for disease diagnosis ( Rajkomar et al, 2019 ; de Gonzalo-Calvo et al, 2020 ; Zhang Z. et al, 2021 ). Unlike the traditional LG-based approach, machine learning can recognize hidden patterns and non-linear interactions in complex data, allowing for a better assessment of clinical outcomes ( Myszczynska et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning algorithms can be applied to help understand large quantities of existing data and to make predictions about new data. Previous studies have used machine learning methods to diagnose or distinguish different types of diseases ( 19 , 20 ). Because of the extremely low incidence of candidaemia, the development of a prediction model requires a very large sample size and must overcome the imbalance between positive and negative results.…”
Section: Introductionmentioning
confidence: 99%